2009
DOI: 10.1016/j.ejpain.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia and early rehabilitation after total knee replacement: A comparison of continuous low‐dose intravenous ketamine versus nefopam

Abstract: The effects of nefopam and ketamine on pain control and rehabilitation after total knee replacement were compared in a prospective, double blinded study. Seventy-five patients were randomly assigned to receive a 0.2mg kg(-1) bolus of nefopam or ketamine, followed by a 120microg kg(-1) h(-1) continuous infusion until the end of surgery, and 60microg kg(-1) h(-1) until the second postoperative day, or an equal volume of saline considered as placebo. Pain scores measured on a visual analog scale at rest and on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 42 publications
(79 reference statements)
1
67
1
1
Order By: Relevance
“…Thus, both ketamine and nefopam prevent neuronal hyperexcitability and reduce morphine consumption. Several studies have shown that both ketamine and nefopam have morphinesparing effects when administered after abdominal surgery [10,13,[17][18][19][20][21][22]. However, ketamine led to lower morphine consumption than nefopam in this study.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, both ketamine and nefopam prevent neuronal hyperexcitability and reduce morphine consumption. Several studies have shown that both ketamine and nefopam have morphinesparing effects when administered after abdominal surgery [10,13,[17][18][19][20][21][22]. However, ketamine led to lower morphine consumption than nefopam in this study.…”
Section: Discussioncontrasting
confidence: 58%
“…Nefopam is a novel type of analgesic drug that exerts non-narcotic effects (1), and thus differs from typical opioids and anti-inflammatory drugs (2). Nevertheless, it effectively elicits antinociception in the majority of noxious and thermal models in rodents (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that ketamine administration both before induction of anesthesia and during surgery markedly reduced the need for opioids, in addition to adequate postoperative analgesia 18 . In some studies that did not assess the combination with remifentanil administered intravenously during the intraoperative period, ketamine decreased pain intensity and opioid consumption postoperatively [31][32][33][34] . From such evidence, protocols were developed to evaluate the combination of ketamine and remifentanil.…”
Section: Discussionmentioning
confidence: 99%